Relaciones familiares y el estado emocional de un adulto mayor de 76 años del cantón Urdaneta - Espinoza León, Evelyn Yuleidy (2023)
The following case study presented aims to analyze how family relationships affect the emotional state, which was carried out in an adult over 76 years of age from the Urdaneta canton because she has problems in her way of relating to others. others and a slight cognitive impairment, which affects him daily, domestic activities are also affected by this problem. To establish the presumed diagnosis of a mild depressive episode, criteria to be met from the international manual for the classification of diseases (ICD-10) were considered. In addition, different psychometric tests were used which provided us with quantitative data on the patient, such as DASS-21, which provided us with a diagnosis on the main symptoms that afflicted the patient, the stress vulnerability test to know how likely it is that the older adult, despite all the activities she performs every day, is vulnerable to suffering a stressful episode. Therefore, and based on the emotional state in which the patient was at the time of carrying out the diagnostic process, a psychotherapeutic scheme was proposed with different techniques under the approach of cognitive behavioral therapy as a possible solution to the patient's problems.